The Influence of Student Activities in Project Based Learning on High School Students' Creative Thinking Abilities in Making Dry Herbariums - Cindy Elvina Ratna Dewati; Saiful Ridlo (Universitas Negeri Semarang, 2024)
One of the government's efforts to support 21st century education is by implementing a new education program known as the independent learning program, one of which is driving schools. One of the dimensions of the Pancasila student profile in driving schools is that students must be able to think creatively. In developing creative thinking skills, students must be active in the learning process so teachers need to design learning patterns that can involve students being active in order to influence creative thinking abilities. The research design used was a pre-experimental design with a one group pre test-post test design. The sampling technique used purposive sampling with a sample size of 45 students. The data collection technique uses tests and observations which are analyzed using quantitative descriptive analysis and simple linear regression analysis. The research results showed that 76% of students were able to reach the medium level creative category, namely in the aspects of flexibility, originality and elaboration. Student activities in project-based learning have a significant effect on students' creative thinking abilities. The influence of student activities in project-based learning on creative thinking skills is 21.1% with a significance level of 0.002 <0.05. There is a positive correlation between student activities in project-based learning and creative thinking abilities. For every 1% increase in student activity scores in project-based learning, the creative thinking ability score increases by 1.440.